Основні результати рятівних археологічних досліджень на поселенні липицької культури поблизу Ганачівки у 2008 р. - Берест, Р.Я. (Археологічні дослідження в Україні, 2009)
The paper presents the main results of rescue archaeological research at the site of Lypytska culture near Hanachivka village in the 2008 season. Based on the factual material the chronological frames of the monument existence and peculiarities of material and spiritual culture have been determined.